Antioxidants Properties of Phyllanthus niruri (Dukung anak) Extracts - A, Ahmeda; Z. (Zhari Ismail), Ismail; A, Gabriel, (Malaysian Journal of Science, 2005)
The antioxidant activity of Phyllanthus niruri (dukung anak) extracts (methanol, water, chloroform), and fractions (ethyl acetate, n-butanol) was evaluated by various antioxidant assays, including total antioxidants, free radical scavenging, superoxide anion radical scavenging, and p-carotene bleaching antioxidant capacity. These various antioxidants activities were compared to standard antioxidant, butylated hydroxy toluene (BHT) and quercetin. Xanthine oxidase (EC 1.1.3.22) inhibition activity of the extracts was also evaluated. The extracts and fractions showed varying degrees of antioxidant activity through all assays. The chloroform extracts exerted a significant activity in the pÃ‚Â¬carotene assay, but no activity in free radical and superoxide anions scavenging were noted. It also showed weak inhibition of xanthine oxidase. The antioxidant property is concentration dependent. The results obtained in the present study indicated P. nirur (dukung anak) leaf extracts are a potential source of natural antioxidants.